PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL TEAM GAMES TOURNAMENT PADA MATERI SIKAPKU PEDULI LINGKUNGAN UNTUK SISWA KELAS II SD - Renny Dwi Puspita; Budi Lestari; I Ketut Suastika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of the Team Games Tournament (TGT) learning model and to improve students’ learning outcomes in Pancasila Education on the topic “My Attitude of Caring for the Environment” for second-grade students at SDN Karangbesuki 3. The study employed a qualitative approach using Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The research subjects were 19 students, consisting of 9 female students and 10 male students. Data were collected through observation, interviews, tests, and documentation. The results showed that the implementation of the TGT learning model significantly improved students’ learning outcomes. The percentage of learning mastery increased from 37% in the pre-cycle to 63% in Cycle I and reached 89% in Cycle II. The class average score also improved from 68 in the pre-cycle to 74 in Cycle I and 85 in Cycle II. In addition, the TGT model enhanced students’ activeness, cooperation, and enthusiasm during the learning process. Therefore, the Team Games Tournament (TGT) learning model is effective in improving Pancasila Education learning outcomes for elementary school students.